Infection control challenges in setting up community isolation and treatment facilities for patients with coronavirus disease 2019 (COVID-19): Implementation of directly observed environmental disinfection. (7th September 2021) - Wong, Shuk-Ching; Leung, Ming; Tong, Danny Wah-Kun; Lee, Larry Lap-Yip; Leung, Will Lok-Hang; Chan, Frank Wan-Kin; Chen, Jonathan Hon-Kwan; Hung, Ivan Fan-Ngai; Yuen, Kwok-Yung; Yeung, Deacons Tai-Kong; Chung, Kin-Lai; Cheng, Vincent Chi-Chung
Abstract: Background: Extensive environmental contamination by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been reported in hospitals during the coronavirus disease 2019 (COVID-19) pandemic. We report our experience with the practice of directly observed environmental disinfection (DOED) in a community isolation facility (CIF) and a community treatment facility (CTF) in Hong Kong. Methods: The CIF, with 250 single-room bungalows in a holiday camp, opened on July 24, 2020, to receive step-down patients from hospitals. The CTF, with 500 beds in open cubicles inside a convention hall, was activated on August 1, 2020, to admit newly diagnosed COVID-19 patients from the community. Healthcare workers (HCWs) and cleaning staff received infection control training to reinforce donning and doffing of personal protective equipment and to understand the practice of DOED, in which the cleaning staff observed patient and staff activities and then performed environmental disinfection immediately thereafter. Supervisors also observed cleaning staff to ensure the quality of work. In the CTF, air and environmental samples were collected on days 7, 14, 21, and 28 for SARS-CoV-2 detection by RT-PCR. Patient compliance with mask wearing was also recorded. Results: Of 291 HCWs and 54 cleaning staff who managed 243 patients in the CIF and 674 patients in the CTF from July 24 to August 29, 2020, no one acquired COVID-19. All 24 air samples and 520 environmental samples collected in the patient area of the CTF were negative for SARS-CoV-2. Patient compliance with mask wearing was 100%. Conclusion: With appropriate infection control measures, zero environmental contamination and nosocomial transmission of SARS-CoV-2 to HCWs and cleaning staff was achieved.